2014
DOI: 10.3233/jid-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Nuances and Management of Multinational Design Teams – a Sino and Occidental Comparison

Abstract: A number of designers of different nationality and design backgrounds were interviewed about their experiences working in teams made up mostly of designers of either a Sino or occidental background. The aim was to identify key issues that are at play with the management of multinational design teams and how they can best be managed for greater success. Key findings included evidence that background (cultural, national and economic) can affect how a designer approached problems and works. This is especially so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They explained that the process of developing TMMs can be influenced by a misunderstanding of team members' roles and responsibilities, a reduced time for a design project, and a long process until the project team gets organizational approval. Furthermore, examining a multinational engineering group, Waal, Newing, and Steele (2014) identified different nationalities, cultures, and languages as major barriers for developing TMMs in the heterogeneous teams. Table 4 summarizes the inhibiting factors in the process of developing TMMs.…”
Section: How Are Team Mental Models Developed Throughout Design Processes?mentioning
confidence: 99%
See 1 more Smart Citation
“…They explained that the process of developing TMMs can be influenced by a misunderstanding of team members' roles and responsibilities, a reduced time for a design project, and a long process until the project team gets organizational approval. Furthermore, examining a multinational engineering group, Waal, Newing, and Steele (2014) identified different nationalities, cultures, and languages as major barriers for developing TMMs in the heterogeneous teams. Table 4 summarizes the inhibiting factors in the process of developing TMMs.…”
Section: How Are Team Mental Models Developed Throughout Design Processes?mentioning
confidence: 99%
“…Bittner and Leimeister (2014) determined that the use of a software system, MindMerger, enabled each member to document and compare their understandings of a specific task with others to develop TMMs by integrating different understandings in the system. Also, Waal et al (2014) showed that information technology communication systems can be necessary for distributed design teams to develop TMMs. Furthermore, Cash, Dekoninck, and Ahmed-Kristensen (2017) explained that in team communication, the process of questioning and giving feedback increases sharedness of TMMs substantially.…”
Section: How Are Team Mental Models Developed Throughout Design Processes?mentioning
confidence: 99%